The Influence of Macroeconomic Factors on Idx-80 Stock Performance for 2020-2023 - Abdullah Safi’i; Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The purpose of this study was to determine the influence of macroeconomic factors on the performance of IDX-80 shares in 2020-2023. This reserach uses time series data in the form of stock performance data, exchange rates, interest rates, inflation, and economic growth from January 2020 to March 2023. Sampling using saturated sampling technique. Research data retrieval techniques using documentation techniques and processed using multiple linear regression analysis model with tools EViews10. Based on the results of the study found that exchange rate variables and economic growth have a positive and significant effect on stock performance. Variable interest rates and inflation rates have no effect on stock performance.